2018
DOI: 10.1192/bji.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study assessing the feasibility of implementing a group cognitive–behavioural therapy-based intervention in Sierra Leone

Abstract: Mental health support in Sierra Leone is sparse, and qualitative research into the feasibility of implementing psychological interventions is equally underdeveloped. Following the 2014 Ebola virus disease outbreak, South London and Maudsley NHS Trust were commissioned to develop a psychological intervention that UK clinicians could train national staff with minimal psychological experience to deliver to their peers. Following the completion of the stepped care, group-based cognitive–behavioural therapy interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 8 publications
0
30
0
2
Order By: Relevance
“…All of the studies described the emotional stress that health professionals [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ], non-specialists working in health care [ [29] , [30] , [31] ], patients [ [32] , [33] , [34] , [35] ], children [ 36 ], and members of the general public experience during a medical pandemic [ 37 , 38 , 39 ]. The first cases of a novel disease to emerge spark fear among health professionals and non-specialists working in health care because little or nothing is known about the disease or how it is transmitted [ 19 , [22] , [23] , [24] , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies described the emotional stress that health professionals [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ], non-specialists working in health care [ [29] , [30] , [31] ], patients [ [32] , [33] , [34] , [35] ], children [ 36 ], and members of the general public experience during a medical pandemic [ 37 , 38 , 39 ]. The first cases of a novel disease to emerge spark fear among health professionals and non-specialists working in health care because little or nothing is known about the disease or how it is transmitted [ 19 , [22] , [23] , [24] , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The one study published to date on the public's psychological reaction to COVID-19 found that although people are feeling more stress and anxiety, positive reactions such as having faith in the future and feeling blessed for what one has have also surfaced [ 37 ]. Faced with uncertainty, it is common for people to seek positive solutions and social and group solidarity to maintain a sense of purpose and cohesiveness [ [19] , [20] , [21] , 25 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Please read Waterman and colleagues (Waterman et al, 2018) for a full description of the three-phased service model. EPSS has accumulated a body of preliminary evidence and feasibility has been indicated (Waterman et al, 2018;Waterman et al, 2019). Amongst those who took part in all phases of EPSS, improvement was observed on all measures of mental health difficulties included (standardised and bespoke).…”
Section: Homerton Covid Psychological Supportmentioning
confidence: 99%
“…• For an example of a CBT-orientated service for frontline disease outbreak staff, see the papers evaluating the Ebola Psychological Support Service (Cole et al, 2020;Waterman et al, 2018;Waterman et al, 2019).…”
Section: Key Practice Pointsmentioning
confidence: 99%
“…Several lessons on mental health service responsiveness to the needs of staff have been learned from past outbreaks. For example, the Ebola Psychological Support Service (EPSS) for healthcare staff was responsively developed during the EVD outbreak (Kamara et al, 2017;Waterman et al, 2018;Waterman et al, 2019). This was a stepped-care approach consisting of several provisions.…”
Section: Lessons On Meeting the Mental Health Needs Of Staffmentioning
confidence: 99%